High-Volume Platelet Distribution: Who Makes the Clinical Decision?. (28th October 2020) - Addams, Joel; Stephens, Laura
Abstract: Anecdotally, many clinicians expect blood components to arrive in standard volumes. Blood components do not come in uniform sizes, however, and institutional experience has revealed platelet units to vary considerably in volume. Since many clinicians are not the ones examining blood products and their volumes prior to transfusion, there is a potential to transfuse a high-volume unit inadvertently to a patient at risk of transfusion-associated fluid overload (TACO), a leading cause of transfusion-related fatalities. The intent of this study was to examine the allocation practices of high-volume platelet units at an academic medical center. Over a six-month period, blood bank technical staff prospectively logged the allocation of high-volume apheresis platelet units with volumes greater than or equal to 400 mL. The staff member who issued the product logged the reason(s), if any, why he or she selected the unit for a particular patient when more than one ABO type-specific product was available. No patient identifiers or data were logged or analyzed in this study. Eighty-seven high-volume platelet units were recorded during the study period. The volumes ranged from 395 to 872 mL, with an average and standard deviation of 571 mL and 92 mL, respectively. Blood bank staff listed the following reasons for their allocation of high-volume platelet unit as follows: the product expiration date in 23 cases (26%), patient age in 13 cases (15%), patient sex in 12 cases (14%), and intraoperative use in 10 cases (11%). This study enumerated the variability in platelet unit volume, with some units containing likely double or triple the volume of the ordering clinicians expectations. Blood bank technologists made clinical decisions in the allocation of high-volume units in three-quarters of the documented cases. This underscores a need to provide clearly-defined guidelines for allocating such units, as well as a mechanism for clinicians to request lower-volume units, particularly for patients at risk of TACO.